2013
DOI: 10.1080/07317115.2012.749323
|View full text |Cite
|
Sign up to set email alerts
|

Is Psychological Vulnerability Related to the Experience of Fraud in Older Adults?

Abstract: Financial exploitation, and particularly thefts and scams, are increasing at an alarming rate. In this study we (a) determined the national prevalence of older adults who report having been a victim of fraud, (b) created a population-based model for the prediction of fraud, and (c) examined how fraud is experienced by the most psychologically vulnerable older adults. The older adults studied were 4,400 participants in a Health and Retirement Study substudy, the 2008 Leave Behind Questionnaire. The prevalence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
77
1
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(92 citation statements)
references
References 16 publications
4
77
1
2
Order By: Relevance
“…The psychologically vulnerable reported fraud at a rate that was 140% higher than the rest of the sample, which means that one out of every 10.3 persons in this group had experienced fraud, compared to one out of 24 for the rest of the sample. These results not only support our previous findings (Lichtenberg et al, 2013) that depressive symptoms and low social-needs fulfillment have an additive effect on fraud predictability, but will serve to remind elder-abuse specialists how broadly psychological vulnerability affects older adults’ lives across a variety of domains. Although social-needs fulfillment and behavioral confirmation were not significant predictors as continuous variables, our analyses indicated that individuals at the extreme ends of these measures were at a higher risk for fraud victimization.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The psychologically vulnerable reported fraud at a rate that was 140% higher than the rest of the sample, which means that one out of every 10.3 persons in this group had experienced fraud, compared to one out of 24 for the rest of the sample. These results not only support our previous findings (Lichtenberg et al, 2013) that depressive symptoms and low social-needs fulfillment have an additive effect on fraud predictability, but will serve to remind elder-abuse specialists how broadly psychological vulnerability affects older adults’ lives across a variety of domains. Although social-needs fulfillment and behavioral confirmation were not significant predictors as continuous variables, our analyses indicated that individuals at the extreme ends of these measures were at a higher risk for fraud victimization.…”
Section: Discussionsupporting
confidence: 88%
“…This study was a direct extension of work by Lichtenberg et al (2013), which examined fraud prediction with both longitudinal and cross-sectional data (social needs measures were only available cross-sectionally). We were able to measure both incidence and prevalence of fraud across a 4-year period and examine in depth the demographic, functional, psychological, and social predictors of new cases of fraud.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We further have only limited knowledge of participant demographics, cognitive capacities, and their life circumstances, although we can infer these with some certainty from prior victim profiling research. Nevertheless, the lack of demographic information for a large part of this specific sample precludes the possibility to investigate the moderating influence of participant characteristics known to influence fraud susceptibility (e.g., Lichtenberg, Stickney, & Paulson, 2013) on the effectiveness of forewarning. This issue should be addressed by future research.…”
Section: Discussionmentioning
confidence: 99%